ARTIFICIAL SOCIALITY AS A CONCEPT AND TECHNOLOGY - Vladimir Menshikov; Oksana Ruza; Anastasiia Simakhova (Baltic Journal of Economic Studies)
The notion of artificial sociality occupies an emerging but still underdeveloped niche at the intersection of artificial intelligence (AI), social theory, and research on human-technology interaction. In contrast to traditional approaches focusing on the cognitive capabilities of AI, artificial sociality focuses on the modeling, reproduction, and transformation of social norms, roles, and forms of behavior within artificial agents and socio-technical systems. The aim of the article is to identify the essence and features of the phenomenon of artificial sociality as a new concept and technology, to determine its impact on social processes and the economy. The methodology of the article on artificial sociality is based on an interdisciplinary approach and includes the analysis of scientific literature, identification of key research areas, and assessment of the impact of technology on social processes and economy. The article discusses artificial sociality as a conceptual framework and as a technological practice. It describes its theoretical foundations, dating back to sociology, cybernetics, and AI ethics, and analyses current implementation examples, from social robots and voice assistants to collective digital platforms. Based on bibliometric analysis, the topic's marginalization is emphasized compared to the dominant discourse focusing on the cognitive aspects of AI. Furthermore, the cultural and disciplinary contexts influencing the development of artificial sociality in different countries are discussed. The authors argue that artificial sociality requires a more integrative and reflexive approach – not only as a technological vector but also as a critical perspective on the role of machines in social life.